Pendampingan Peningkatan Pemahaman Dan Praktik Ibadah Santri Melalui Kajian Kitab Sulam At-Taufiq Di Pondok Pesantren Al Urwatul Wutsqo Jombang - Qurrotul Ainiyah; Dita Dzata Mirrota; Moch. Sya’roni Hasan; Julianne Kamelia Riza; Ahmad Budiyono (An Naf'ah: Jurnal Pengabdian Masyarakat, 2025)
This community service aims to improve the understanding and practice of worship through the Sulam At-Taufiq book for students at Al Urwatul Wutsqo Islamic Boarding School in Jombang. This activity focuses on assisting santri in understanding the text of the book and practicing thaharah and prayer correctly. The method used includes a comprehensive and interactive approach through seven stages: identification of needs, pre-test, program design, classical learning, selection of superior santri as companions, worship practices, and evaluation and follow-up. The results of the service showed a significant improvement in the ability of santri to read and understand the Sulam At-Taufiq book, including the ability to interpret, analyze in terms of Nahwu and Sharaf, and understand the meaning of its contents. The students also showed an increase in skills in the practice of thaharah and prayer according to Islamic law. Supporting factors for the success of the program are the high interest and enthusiasm of the santri, while time constraints are a limiting factor. This program succeeded in creating a sustainable mentoring system by empowering senior santri as mentors